2020
DOI: 10.1016/j.yebeh.2020.107442
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of anxiety in epilepsy during coronavirus disease (COVID-19) pandemic

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has affected people globally, and people with chronic diseases are suffering more in maintaining their mental and physical health. Method: This cross-sectional, case-control study assessed the anxiety level in people with epilepsy compared with the general population. Results: The results showed that 13.5% of patients had experienced a severe level of anxiety, but the mean anxiety level between groups did not show significant difference. Conclusion: Although sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Hao et al reported that PWE with refractory epilepsy experience more psychosocial distress compared to healthy individuals 13 . However, other authors found that the anxiety level of PWE was not significantly higher than that of the general population 14 .…”
Section: Resultsmentioning
confidence: 78%
“…Hao et al reported that PWE with refractory epilepsy experience more psychosocial distress compared to healthy individuals 13 . However, other authors found that the anxiety level of PWE was not significantly higher than that of the general population 14 .…”
Section: Resultsmentioning
confidence: 78%
“…Ozamiz-Extebarria et al (2020) reported that, in Spain, younger individuals with chronic diseases complained more of symptoms related to anxiety and depression during the arrival of the virus and consequent confinement than the rest of the population [ 49 ]. Additionally, the presence of a chronic disease as a risk factor for anxiety and depression during the COVID-19 pandemic has been observed by Ping et al (2020, 29] in the general population in China and by Salari et al (2020) in patients with Parkinson’s Disease [ 48 ] and Epilepsy [ 51 ] in Iran. Participants with immunocompromised or immunosuppressed status were an exception in our sample as these individuals have more frequent intrusive symptoms than those who are not immune-deficient.…”
Section: Discussionmentioning
confidence: 99%
“…9 Relevant treatment should be continued and positive psychology management is beneficial. 10 More importantly, urinary urge/incontinence and increased motor fluctuations are commonly observed in PD patients, perhaps partly due to pharmacokinetic issues. 11 In our case, the patient was not able to tell the difference in her urinary symptoms but she had a urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%